USE OF INSECTS AS AN ALTERNATIVE FOR HUMAN FOOD - Xavier, Robson Henrique Coelho; Edemar Ferrarezi Junior; Caracini, Luiz Gustavo (Revista Interface Tecnológica, 2023)
By definition, entomophagy is the act of eating insects. This practice by human beings is a reality in several countries; nevertheless, national governments have failed to promote insect-eating. The use of insects as part of a food source has become increasingly common as it provides three important benefits to society, such as nutritional properties, environmental factors and socioeconomic advantages. Edible insects are a major protein source, which, in many cases, contain a higher level of that substance when compared to other animals and/or vegetables, normally used in human diet. Based on this idea, this work aims, through qualitative bibliographical research, to discuss the use of insects in human eating habits, as well as its advantages, forms of use, conservation and preparation.